2011
DOI: 10.1590/s0080-62342011000200023
|View full text |Cite
|
Sign up to set email alerts
|

O brincar em sala de espera de um Ambulatório Infantil: a visão dos profissionais de saúde

Abstract: Portuguese / English: www.scielo.br/reeusp RESUMO O objetivo deste estudo foi compreender, na perspectiva dos profissionais de saúde, o significado do uso do brincar/brinquedo em sala de espera de um ambulatório infantil. Realizaram-se entrevistas semiestruturadas com 11 trabalhadores. Procedeu-se à análise qualitativa dos dados, organizados ao redor de dois temas: reconhecimento da importância do brincar/brinquedo e lidando com limitações. O brincar mostra-se como uma estraté-gia de cuidado à criança, pois am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
5
0
4
Order By: Relevance
“…Estudo realizado por Nascimento et al 11 destaca que o brincar durante a espera por atendimento auxilia as crianças e seus acompanhantes a amenizar os fatores negativos gerados pela ociosidade. De acordo com os autores, quando há brincadeiras, ocorrem mudanças positivas no comportamento das crianças e acompanhantes, tais como diminuição da ansiedade, nervosismo, cansaço, agitação e impaciência, demonstração de alegria, tranquilidade e bom humor, além de facilitar a interação e comunicação entre crianças e a equipe de saúde.…”
Section: Discussionunclassified
“…Estudo realizado por Nascimento et al 11 destaca que o brincar durante a espera por atendimento auxilia as crianças e seus acompanhantes a amenizar os fatores negativos gerados pela ociosidade. De acordo com os autores, quando há brincadeiras, ocorrem mudanças positivas no comportamento das crianças e acompanhantes, tais como diminuição da ansiedade, nervosismo, cansaço, agitação e impaciência, demonstração de alegria, tranquilidade e bom humor, além de facilitar a interação e comunicação entre crianças e a equipe de saúde.…”
Section: Discussionunclassified
“…The ludicrous in the waiting room not only valor the child's developing process but is also a strategy towards health promotion as it improves communication and interaction with health professionals 16 . The children, on relating their participation in the waiting room activities of this research, show that this environment is little explored in health services:…”
Section: Sometimes It Is Boring Staying Here and Wait There Is Nothimentioning
confidence: 99%
“…In studies on playing in the waiting room, in the viewpoint of health professionals, it was found that the professionals recognize de advantages pf using toys, many confirmed not to use it frequently with children 16 . It becomes necessary for professional formation to include humanistic principles to stimulate creativity and adopt ludicrous strategies for the assisting children, understanding this activity as an integral part of health care for this population 16 .…”
Section: Did Not (Participate In the Waiting Room Activity) (C1) I mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar fi ndings were found in a study of children in child outpatient waiting room, in which the interviewees acknowledged the benefi ts of playing for children. However, lack of time was one of the reasons described which hindered the realization of play (20) . Thus, it becomes imperative to reorganize the work process in health facilities, so the children's play is not taken as a secondary aim in healthcare practice with children, but accepted as an integral part of the care of these little ones.…”
Section: Barriers May Come From the Staff That Sometimes Fi Nd Play Umentioning
confidence: 99%